2003
DOI: 10.1016/s0002-9440(10)63672-3
|View full text |Cite
|
Sign up to set email alerts
|

Variations in ATM Protein Expression During Normal Lymphoid Differentiation and Among B-Cell-Derived Neoplasias

Abstract: The ataxia telangiectasia mutated (ATM) protein plays a central role in the cellular response to DNA double-strand breaks (DSBs). Developmentally programmed DSBs are restricted to cellular subsets within lymphoid tissues and we asked whether ATM expression is differentially regulated during lymphoid differentiation. We showed that immature B cells in bone marrow and immature T cells of the thymic cortex were negative or weakly ATM-positive. T cells of thymic medulla and peripheral tissues strongly expressed AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Fas resistance in this system is due to the aberrant up-regulation of FLIP proteins. 26,27 Conversely, ATM expression and function are impaired in many HL cases 7 and in several HL-derived cell lines. 9,29 To test whether ATM loss of function may contribute to Fas resistance through FLIP protein up-regulation, we took advantage of a lymphoma cell line, L428, that has been previously characterized for the aberrant down-regulation of ATM activity 29 and for the aberrant up-regulation of FLIP protein levels.…”
Section: Atm Kinase Activity Sensitizes Hodgkin Lymphoma Cells To Fasmentioning
confidence: 99%
See 2 more Smart Citations
“…Fas resistance in this system is due to the aberrant up-regulation of FLIP proteins. 26,27 Conversely, ATM expression and function are impaired in many HL cases 7 and in several HL-derived cell lines. 9,29 To test whether ATM loss of function may contribute to Fas resistance through FLIP protein up-regulation, we took advantage of a lymphoma cell line, L428, that has been previously characterized for the aberrant down-regulation of ATM activity 29 and for the aberrant up-regulation of FLIP protein levels.…”
Section: Atm Kinase Activity Sensitizes Hodgkin Lymphoma Cells To Fasmentioning
confidence: 99%
“…6 More interestingly, ATM expression is aberrantly low in several B-and T-cell lymphomas irrespective of A-T genotype. [7][8][9][10] Fas (CD95/APO-1) is a transmembrane protein belonging to the tumor necrosis factor superfamily. Upon binding of Fas ligand or agonistic antibodies, the Fas receptor recruits several cytosolic proteins to form the death-inducing signaling complex (DISC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular ATM expression is strongly reduced or lost in some leukaemia and lymphoma [73,[111][112][113]. The modulation of ATM expression levels in breast cancer has been largely investigated.…”
Section: Atm Expression and Cancermentioning
confidence: 99%
“…26,27 ATM, which is involved in the cellular responses to double-strand breaks, is normally expressed in pre-GC B cells and it has been suggested that inactivation of the gene may be involved in malignant transformation. 28,29 In MCL, it has been assumed that Cyclin D1 primarily acts through its role in the cell cycle, controlling the transition of G 1 to S phase by binding and activating cyclin-dependent kinase (CDK) 4 and CDK6 followed by phosphorylation of the retinoblastoma protein and release of the transcription factor E2F. 30 However, in other malignancies several CDK-independent functions of Cyclin D1 have been identified, including interaction with the pro-apoptotic protein BAX 21 and RAD51, 31 the latter impacting DNA repair.…”
mentioning
confidence: 99%